Learning Urbanism with board games: An experience in Universidade Portucalense - Florentino, Rui (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
There are many combinations of Urbanism with Games, but the issues to understand the cities, their planning, project and government, are usually very complex. This work presents the application of a game that stimulates the architecture students for the integrated knowledge of urban planning. The experience of this ludic activity, extended by some academic exercises in continuity, allows to discuss several relevant questions, as the scale, the indicators and aspects of economy and environment. The results show that there is also the potential to improve the professional practices, especially in urban and territorial management.